Degradation analysis of commercial interconnect materials for solid oxide fuel cells in stacks operated up to 18000 hours. (29th November 2019) - Bianco, Manuel; Ouweltjes, Jan Pieter; Van herle, Jan
Abstract: Despite being a mature technology, solid oxide fuel cell (SOFC) devices are still limited by lifetime issues. In SOFC stacks, cell/interconnect interaction is the main responsible for voltage degradation at the oxygen electrode side. Corrosion and chromium evaporation might in fact increase ohmic and charge transfer losses. This study presents the evolution of the degradation phenomena inside four SOFC short-stacks tested respectively for 45, 2700, 4800 and 10000 hours. An additional stack which underwent 124 thermal cycles is also analyzed to assess the mechanical reliability of the interconnect/ceramic coupling. Metal interconnect was made of K41/AISI441 ferritic stainless steel coated with MnCo2 O4 porous barrier layer. Scanning electron microscope (SEM) coupled with energy dispersive X-ray spectroscopy (EDS) characterization is applied to examine the degradation process. Observations indicate that despite a harsh initial red-ox interaction between the cathode materials and the interconnect, after 5000 h of operation the kinetic of the degradation process in the electrical contact areas slows down dramatically. An empirical model based on the scale thickness at different interconnect location gives estimation for the oxide thermal growth for a stack lifetime period. From the mechanical properties point of view, no spallation was observed and local delamination was mainly due to the sample preparation process. Highlights: The stack survives the degradation caused by perovskite/interconnect interaction. The degradation at the air side of the interconnect stabilizes after 5000 h. The tested SOFC stack is robust: it can withstand more than 120 thermal cycles. The results partially disaffirm the reliability of ex-situ tests on interconnects.